PRINCIPALS’ INSTRUCTIONAL SUPERVISORY PRACTICES ON STUDENTS’ ACADEMIC PERFORMANCE IN MATHEMATICS IN PUBLIC SECONDARY SCHOOLS IN KILUNGU SUB-COUNTY, KENYA - COLLETA NGAMI KUMONYA (Machakos University Press, 2025)
Kilungu Sub-County faces significant challenges in the educational sector, particularly concerning students' performance in Mathematics. Despite efforts to improve educational outcomes, students continue to struggle with understanding and applying mathematical concepts, leading to subpar academic achievement. The purpose of this study was to establish the effect of principals’ instructional supervisory practices on students’ academic performance in Mathematics in public secondary schools in Kilungu Sub- County, Kenya. The research was guided by four objectives: to examine the effect of principals’ supervision of professional records, principals’ classroom visitation, principals’ instructional leadership, and principals' provision of teacher professional development, on students’ academic performance in Mathematics in public secondary schools in Kilungu Sub-County, Kenya. The research was guided by instructional leadership theory. A correlational research design was adopted. The study focused on 20 public secondary schools in Kilungu Sub-County, Makueni County, Kenya, with the target population comprising 20 principals, 66 Mathematics teachers, and 800 students. Stratified random sampling was employed to select six schools. A simple random sampling technique was used to select 21 Mathematics teachers and 249 Form Three students. Both interviews and questionnaires were used to gather data. Content analysis was used to analyze the qualitative data from the interviews. The study found that principals’ instructional supervisory practices significantly influenced students’ academic performance in Mathematics. Specifically, the supervision of professional records promoted accountability and instructional alignment, leading to better student outcomes. Classroom visitation encouraged learner engagement and provided teachers with useful feedback, though it was underutilized for professional development. Instructional leadership by principals contributed to improved lesson delivery and academic support, despite some inconsistencies in promoting collaborative teaching cultures. The provision of teacher professional development enhanced teaching effectiveness, though challenges such as limited funding and insufficient follow-up were noted. The study concluded that all four supervisory domains were positively associated with improved Mathematics performance. It recommended strengthening record supervision, institutionalizing structured classroom visitation, promoting collaborative instructional leadership, and prioritizing need-based teacher development. The research also advocated for strategic policy support to reduce principals’ administrative burdens and enhance their focus on instructional leadership. These findings provide a practical framework for improving educational outcomes through targeted leadership interventions in public secondary schools.